Regulatory Mechanisms of the RNA Modification m6A and Significance in Brain Function in Health and Disease - Mathoux, Justine; Henshall, David C.; Brennan, Gary P. (Frontiers in Cellular Neuroscience, 2021)
RNA modifications have emerged as an additional layer of regulatory complexity governing the function of almost all species of RNA. N6-methyladenosine (m6A), the addition of methyl groups to adenine residues, is the most abundant and well understood RNA modification. The current review discusses the regulatory mechanisms governing m6A, how this influences neuronal development and function and how aberrant m6A signaling may contribute to neurological disease. M6A is known to regulate the stability of mRNA, the processing of microRNAs and function/processing of tRNAs among other roles. The development of antibodies against m6A has facilitated the application of next generation sequencing to profile methylated RNAs in both health and disease contexts, revealing the extent of this transcriptomic modification. The mechanisms by which m6A is deposited, processed, and potentially removed are increasingly understood. Writer enzymes include METTL3 and METTL14 while YTHDC1 and YTHDF1 are key reader proteins, which recognize and bind the m6A mark. Finally, FTO and ALKBH5 have been identified as potential erasers of m6A, although their in vivo activity and the dynamic nature of this modification requires further study. M6A is enriched in the brain and has emerged as a key regulator of neuronal activity and function in processes including neurodevelopment, learning and memory, synaptic plasticity, and the stress response. Changes to m6A has recently been linked with Schizophrenia and Alzheimer disease. Elucidating the functional consequences of m6A changes in these and other brain diseases may lead to novel insight into disease pathomechanisms, molecular biomarkers and novel therapeutic targets.